Mazamisa’s Dialectica-Reconciliae and Mosala’s Materialistic Reading of the Text: An Experimental Exploration of Luke 12:13-21 - Hombana, Mphumezi (Hervormde teologiese studies, 2024)
This article explores the interpretive dimensions of Luke 12:13-21 within the landscape of the first-century world and how it relates to the democratic South African context. The question that drives this reading is two-fold: (1) How would this parable be understood by the early Jesus movement in the first-century Mediterranean context? In the light of socio-economic, religious, and political context of the day? What did they hear from what Jesus said through this parable? (2) similarly, what are we hearing from this same parable in today’s society, in the light of our own socio-economic, religious and political landscape? I suggest analysing this parable through Mazamisa’s dialectica reconciliae and Mosala’s historical-materialistic lenses, which might reveal profound insights into the nation’s post-1994 journey of reconstruction and development of South Africa and the liberation of the black child, in a government led by another black child. The passage’s warnings against materialism and its call to be ‘rich towards God’ resonate with South Africa’s pursuit of social justice and equitable wealth distribution. It mirrors concerns over land reform and responsible inheritance, aligning with the principles of Ubuntu that emphasize collective well-being. The text’s emphasis on spiritual values contributes to discussions on fostering a cohesive national identity amid religious diversity. It underscores the importance of transparent governance and accountability, addressing wealth disparities, and confronting poverty. This exploration offers a compelling synthesis, suggesting how Luke 12:13-21 can guide South Africa in forging a just, inclusive, and spiritually grounded democratic society.ContributionThis study explores the interpretive dimensions of Luke 12:13-21 within the context of the first-century world and its relevance to South Africa, offering profound insights into post-1994 reconstruction and development, social justice, equitable wealth distribution, collective well-being, national identity, wealth disparities, and poverty, ultimately guiding South Africa towards a just, inclusive, and spiritually grounded democratic society.